PENGARUH EKSTRAK FENOLIK ANTIFOTOOKSIDAN DAUN KESUM (Polygonum minus) TERHADAP STABILITAS EMULSI PADA MINYAK RBDPO (REFINED BLEACHED DEODORIZED PALM OIL ) DALAM AIR - Mario Silalahi; Yohana Sutiknyawati Kusumadewi; Henny Sulistyowati (Perkebunan dan Lahan Tropika, 2022)
This study aimed to obtain the type of solvent that has optimal activity antiphotooxidaion to inhibit photooxidation RBDPO oil, and determine the effect of phenolic extracts of the kesum leaf on RBDPO oil emulsion stability.The study consisted of two steps. The first steps make kesum leaf extract with methanol, n-hexane fraction, ethyl acetate fraction, the fraction of methanol and methanol-water fraction.Each extract with a concentration of 1000 ppm RBDPO emulsified into the oil, then proceed with testing antiphotooxidation activity and total phenol content using a completely randomized design consisting of a treatment factor is the type of preparation (S) consisting of methanol extract (s1), hexane fraction (s2), ethyl acetate fraction (s3), methanol fraction (s4), methanol-water fraction (s5) is repeated three times.Observation variables involved testing antiphotooxidation activity and total phenol content.The second steps is the preparation antiphotooxidant best on first steps, the extract concentration (0, 500, 1000, 1500, 2000, 2500 and 3000 ppm)emulsified into the RBDPO oil, then proceed with testing antiphotooxidation activity and emulsion stability on RBDPO oilusing regression correlation, each treatment was repeated three times.The results of first steps study is the best type of preparation with methanol extracts with antiphotooxidation activity of 47.42% and total phenol of 22.03 mg GAE/g.The results of second steps study showed that increasing the concentration of the methanol extract significantly affected the antiphotoxidantion activity while methanol extract concentration no significantly effect on the stability of emulsion RBDPO in water.Emulsion stability was measured on days 0, 1, 2, 3, and showed no significantly effect.Emulsion stability did not change until three day, showed that the type of surfactant Tween 20 were used effectively in the system RBDPO palm oil emulsion in water.